Fuel cell and ultra-capacitor hybridization: A prototype test bench based analysis of different energy management strategies for vehicular applications - Vural, B.; Boynuegri, A. R.; Nakir, I.; Erdinc, I.; Balikci, A.; Uzunoglu, M.; Gorgun, H.; Dusmez, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
An energy storage system with sufficient power capacity should be incorporated with fuel cells (FCs) to compensate the slow dynamics of FCs. Ultra-capacitors (UCs) are potential candidates for a solution in this aspect. A test bench of such an FC/UC hybrid configuration that can emulate the dynamics of vehicular systems is presented in this paper. Namely, the test bench performance verification of wavelet transform and fuzzy logic based energy management strategy that was discussed in earlier simulation-based studies of the authors is investigated. Of equal importance is the comparison of the cascade wavelet-fuzzy logic based strategy with the case of using only fuzzy logic in the energy management is presented. Experimental results with small-scale devices, a PEMFC (5 kW, 48 V) manufactured by Plug Power (R) Company, and a UC bank composed of 430 F, 16 V and 165 F, 48 V UC modules manufactured by Maxwell Technologies (R) Company, illustrate the successful performance analysis of employed energy management schemes during similar motor cycles. (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: Energy management; Fuzzy logic; Wavelet transform; PEM fuel cell; Ultra-capacitor; Vehicular application; FUZZY-LOGIC; SYSTEM; MODEL; PERFORMANCE; BATTERY; Chemistry; Electrochemistry; Energy & Fuels